4 - Beyond the Impasse of African Industrial Development: The Case of Botswana, Tanzania and Zambia - Kapunda, Stephen Miti (Africa Development, 2007)
The thrust of this article is to examine critically the importance, performance and under-weighting of the industrial sector in Africa focusing on three coun- tries, Botswana, Tanzania and Zambia, in the Southern African Development Community (SADC) region. The article shows that both theoretical and empiri- cal evidence indicates somewhat unsatisfactory industrial performance. The ar- ticle attempts to explain the way forward (beyond the impasse), by providing alternative approaches, opportunities and recommendations.